Adoption of improved citrus orchard management practices: a micro study from Drujegang growers, Dagana, Bhutan. Issue 1 (December 2016) - Dorji, Kinley; Lakey, Lakey; Chophel, Sonam; Dorji, Sonam; Tamang, Birkha
Abstract Background Citrus ranks top among the agricultural export commodities of Bhutan both in terms of volume and value. However, citrus cultivation practices still remain traditional with very low yield and inferior fruit quality. This study adopted community approach to identify basic components of citrus orchard management. Citrus growers of Drujegang were trained on citrus orchard management and assessed the impact of training on the adoption of management technology and subsequent effect on the yield and household (HH) income for 40 randomly selected individuals. Results Statistical results showed significant difference both in terms of adoption of improved orchard management practices (p = 0.04) and HH income generation (p = 0.01). Adoption of improved management practices increased from 4.54 % (in 2012) to over 16 % (in 2014) with a mean yield increase of 27.5 % (212 kg acre−1 ) over previous year. Similarly, mean production increased from 5376 (2012) to 11, 993 (2014) kg HH−1 . Thus, average annual HH income from the sale of citrus increased from Nu. 82, 641 (in 2012) to 164, 307 (in 2014). Conclusions Hands-on training on basic orchard management increased the rate of adoption and resulted in increased yield and production. Huge potential exists in enhancing the livelihood of citrus growers by taking forward the available orchard management technology to growers through appropriate research and extension intervention. Therefore, replication of similar participatory approach at community level is recommended in other parts of the country.